A Model for Efficiency Estimation of Routing Protocols for Ad-hoc Network - Saroj, Suman; Tiwari, Raj Gaurang; Kumar, Pankaj (International Journal of Computer Sciences and Engineering, 2025)
Mobile computing is a new computing paradigm that embeds time, place and person in computing. The combination of networking and mobility induces a new dimension to the application and services. Communications over network consume energy resources of the network. Therefore it is essential to have mechanism that consume fewer resources over network. Comforting communication is the strategy that can improve the life of network by saving resources. Comforting communication is identified as a process by which users contribute and mingle resources relating to transmission of data to improve their performances. In this paper, we proposed a Capacity-Enriched Comforting topology control scheme that considers both upper layer network capacity and physical layer relay selection in comforting communications.